Answer:
That may be one of the answers but it is check all that apply
Step-by-step explanation:
the values in the table represent a linear function. what is the common difference of the associated arithmetic sequence?
x: 1, 2, ,3 ,4 ,5
y: 6, 22, 38, 54, 70.
A) 1
B) 20
C) 16
D) 5
Answer:
c
Step-by-step explanation:
You can find that 22-6=38-22=54-38=70-54=16
so the answer is c 16
Answer: The correct opion is
(C) 16.
Step-by-step explanation: Given that the values in the following table represent a linear function.
x: 1, 2, 3, 4, 5
y: 6, 22, 38, 54, 70.
We are to find the common difference of the associated arithmetic sequence.
If y = f(x) is the given function, then we see that
f(1) = 6, f(2) = 22, f(3) = 38, f(4) = 54 and f(5) = 70.
So, the common difference of the associated arithmetic sequence is given by
[tex]f(2)-f(1)=22-6=16,\\\\f(3)-f(2)=38-22=16,\\\\f(4)-f(3)=54-38=16,\\\\f(5)-f(4)=70-54=16,~~~\cdots.[/tex]
Thus, the required common difference of the associated arithmetic sequence is 16.
Option (C) is CORRECT.
What type of number can be written as a fraction plq, where p and q are integers
and q is not equal to zero?
A. 7
B. All numbers can written in this way
C. A rational number is
D. An irrational number
Answer:
rational number
Step-by-step explanation:
written as a fraction p/q, where p and q are integers and q is not equal to zero, is called as rational numbers. Example - 4/5, 2, 100, 1/7 etc all are rational numbers.
Z varies directly with x and inversely with y. What happens to Z when both x and y are doubled? z stays the same. z is halved. z doubles. z is squared.
Answer:
z stays the same
Step-by-step explanation:
From the statements
z ∝ x and z ∝ 1/y
Combining both proportions
z ∝ x/y
z = k * (x/y)
The above equation defines the relationship between x,y and z
k is the proportionality constant.
Lets say that x and y are doubled
Then
z = k * (2x/2y)
2 in the numerator and denominator will be cancelled out
z = k * (x/y)
Therefore we can conclude that z will stay the same if x and y are doubled ..
Answer:
z stays the same
Step-by-step explanation:
We have been given that z varies directly with x and inversely with y.
Thus, we have the equation
[tex]z=\frac{kx}{y}...(i)[/tex]
Here k is constant of proportionality.
Now, x and y both are doubled, thus, the equation becomes
[tex]z=\frac{k(2x)}{2y}[/tex]
Cancel 2 from numerator and denominator
[tex]z=\frac{kx}{y}[/tex]
This is same as equation (i)
Hence, we can conclude that z remains same.
first option is correct.
The base of a right circular cylinder has a diameter of 5.00 inches. Sally measured the circumference of the base cylinder and recorded it to be 15.5 inches. What is the percent of error in her measurement? Express your answer to the nearest tenth of a percent.
Please explain what you did to get your answer!
Answer:
The percent of error in her measurement is 1.3%
Step-by-step explanation:
we know that
The circumference of a circle is equal to
[tex]C=\pi D[/tex]
where
D is the diameter
we have
[tex]D=5\ in[/tex]
assume
[tex]\pi=3.14[/tex]
substitute
[tex]C=(3.14)(5)=15.7\ in[/tex] ----> This value represent the 100% (theoretical value)
Find the difference between the theoretical value and the measured value
[tex]15.7-15.5=0.2\ in[/tex]
Find the percentage by proportion
[tex]15.7/100=0.2/x\\ x=100*0.2/15.7\\ x=1.3\%[/tex]
What is the product?
(7x2y^3)(3x^5=y^8)
Answer:
is the equal sign supposed to be there? if it wasnt then answer would be 42x^6y^11
Step-by-step explanation:
find the area of the parallelogram answer option 15 25 30 44
There is no picture of the parallelogram needed to answer this question.
Factor 6(x − 4)2 − (x − 4) − 2 completely.
A (6x − 25)(x − 2)
B (3x − 14)(2x − 7)
C (3x − 2)(2x + 1)
D 2(x − 5)(3x − 11)
Answer:
B (3x − 14)(2x − 7)
Step-by-step explanation:
6(x − 4)^2 − (x − 4) − 2
Replace x-4 with m
6m^2 − m − 2
(3m -2 ) (2m+1)
Now replace m with x-4
(3 (x-4) -2) (2(x-4) +1)
Distribute
(3x-12 -2) (2x-8+1)
Combine like terms
(3x-14) (2x-7)
Which rotation maps point K(8,-6) to K(-6, -8)?
Answer:
90 degree clockwise rotation about (0,0).
Step-by-step explanation:
That would be a clockwise rotation of 90 degrees about the origin (0,0).
The rotation that maps point K(8,-6) to K(-6,-8) is a counterclockwise rotation of 90 degrees about the point (0,0).
What is the transformation of geometry over the coordinate plane?Transform the shapes on a coordinate plane by rotating, reflecting, or translating them. Felix Klein introduced transformational geometry, a fresh viewpoint on geometry, in the 19th century.
Here,
To find the rotation that maps point K(8,-6) to K(-6,-8), we can use the following steps,
Plot the points K(8,-6) and K(-6,-8) on a coordinate plane.
Since point K(8,-6) is being mapped to point K(-6,-8), the rotation must be counterclockwise. As rotation about the origin with angle 90 gives the transformation equation,
(x, y) ⇒ (y, -x)
Therefore, the rotation that maps point K(8,-6) to K(-6,-8) is a counterclockwise rotation of 90 degrees about the point (0,0).
Learn more about transformation here:
brainly.com/question/18065245
#SPJ6
through: (1,-5), perpendicular to y=18x+26
Answer:
Step-by-step explanation:
If you're asking for the equation of a line that goes through (1,-5) and is perpendicular to y=18x+26 here's what you do.
1. find the slope of the new line by taking the negative reciprocal of the slope of the first line ([tex]-\frac{1}{18}[/tex])
2. plug in the point (1,-5) and the new slope into the point slope form equation
[tex]y_{2} -y_{1}=m(x_{2}-x_{1})[/tex]
3.Now that you have y-(-5)= -1/18(x-1) simplify
3.a y-(-5)= -1/18x + 1/18
3.b y=-1/18x - 89/18
4. final equation you get is y = -1/18 - 89/18
What are the solutions to the system of equations?
Answer:
A
Step-by-step explanation:
Given the 2 equations
y = x² - 4x + 8 → (1)
y = 2x + 3 → (2)
Since both express y in terms of x we can equate the left sides, that is
x² - 4x + 8 = 2x + 3 ( subtract 2x + 3 from both sides )
x² - 6x + 5 = 0 ← in standard form
(x - 1)(x - 5) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x - 5 = 0 ⇒ x = 5
Substitute these values into (2) for corresponding values of y
x = 1 : y = (2 × 1) + 3 = 2 + 3 = 5 ⇒ (1, 5)
x = 5 : y = (2 × 5) + 3 = 10 + 3 = 13 ⇒ (5, 13)
Solutions are (1, 5) and (5, 13)
Answer:
A. [tex](1,5)[/tex] and [tex](5,13)[/tex]
Step-by-step explanation:
We have been given a system of equations. We are asked to find the solution of our given system.
[tex]\left \{ {{y=x^2-4x+8}\atop {y=2x+3}} \right.[/tex]
Equate both equations:
[tex]x^2-4x+8=2x+3[/tex]
[tex]x^2-4x-2x+8-3=2x-2x+3-3[/tex]
[tex]x^2-6x+5=0[/tex]
Split the middle term:
[tex]x^2-5x-x+5=0[/tex]
[tex]x(x-5)-1(x-5)=0[/tex]
[tex](x-5)(x-1)=0[/tex]
Use zero product property:
[tex](x-5)=0\text{ (or) }(x-1)=0[/tex]
[tex]x=5\text{ (or) }x=1[/tex]
Now, we will substitute both values of x, in our given equation to solve for y.
[tex]y=2x+3[/tex]
[tex]y=2(1)+3[/tex]
[tex]y=2+3[/tex]
[tex]y=5[/tex]
One solution: [tex](1,5)[/tex]
[tex]y=2x+3[/tex]
[tex]y=2(5)+3[/tex]
[tex]y=10+3[/tex]
[tex]y=13[/tex]
2nd solution: [tex](5,13)[/tex]
Therefore, option A is the correct choice.
Please help with this question! 25 points will be rewarded.
Answer:
C. 2x - 3(-3x - 4) = -21.
Step-by-step explanation:
y + 3x = -4
2x - 3y = -21
From the first equation y = -3x - 4.
Substituting this for y in the second equation, we have:
2x - 3(-3x - 4) = -21.
Ivuviivivivvivuvuccucucyc
asdfghauyrugvo bnidfassfasag
HELP me please !! I really need it
Answer:
D
Step-by-step explanation:
To find the critical values , that is the zeros
Solve the quadratic
x² - x - 20 = 0 ← in standard form
Consider the factors of the constant term (- 20) which sum to give the coefficient of the x- term (- 1)
The factors are - 5 and + 4, since
- 5 × 4 = - 20 and - 5 + 4 = - 1, hence
(x - 5)(x + 4) = 0
Equate each factor to zero and solve for x
x - 5 = 0 ⇒ x = 5
x + 4 = 0 ⇒ x = - 4
Thus the critical values are - 4, 5 → D
Answer:
D. -4, 5
Step-by-step explanation:
x² - x - 20 factorised = (x - 5) (x + 4)
In order to get the answers, you have to make each bracket equal zero.
(x - 5) = x = 5
(x + 4) = x = -4
The crucial numbers are -4 and 5.
Hope this helps!
how many possible outcomes are there when you roll five dice?
Answer:
i think the answer is 7776
for two dice its 6x6 36 then 36×6 216 then 216×6 1296 then 1296×6 7776
Answer: 7776 possible outcomes
Step-by-step explanation:
You know that each dice has 6 possible results.
1, 2, 3, 4 , 5 , 6
Then, if you throw 2 dice, the possible results are 6(for the first one)*6(for the second one) = 6*6 = 36
then, as you add another die, you add another 6 to that equation, this means that for 5 dice we have
combinations = 6*6*6*6*6 = 6^5 = 7776
But in this situation most of the numbers can be repeated, for example, then number 6, can be made from (1 + 1 + 1 + 1 + 2), (1 + 2 + 1 + 1 + 1), (1 + 1 + 1 + 2 + 1 +1)
etc, this means that the die that rolls a 2 can change, but the end result of the addition is the same, in this case the total range of possible values is the amount of dice times the biggest value minus the amount of dice times the smallest value:
5*6 - 5*1 = 30 - 5 = 25 possible results
So you have 7776 combinations that give a only 25 possible results (a number between 5 and 30)
You want to produce a scale drawing of your living room, which is 24 ft by 15 ft. If you use a scale of 4 in. = 6 ft, what will be the
dimensions of your scale drawing?
Answer:
The dimensions of the living room is the scale drawing are 16 in by 10 in
Step-by-step explanation:
we know that
The scale drawing is equal to
[tex]\frac{4}{6}\frac{in}{ft}[/tex]
That means ----> 4 inches in the drawing represent 6 feet in the real
so
Find the dimensions of the living room in the scale drawing
using proportion
For 24 ft
[tex]\frac{4}{6}\frac{in}{ft}=\frac{L}{24}\frac{in}{ft}\\ \\L=4*24/6\\ \\L=16\ in[/tex]
For 15 ft
[tex]\frac{4}{6}\frac{in}{ft}=\frac{W}{15}\frac{in}{ft}\\ \\L=4*15/6\\ \\W=10\ in[/tex]
therefore
The dimensions of the living room is the scale drawing are 16 in by 10 in
Kayla rolls a die 84 times. How many times can she expect to roll a 3?
Answer:
14
Step-by-step explanation:
Assuming the die is 6 sided, there are only 6 possible rolls she can get. And assuming that this is a perfect world where probability is perfect, she will roll each number 14 times, because 84/6 is 14.
Final answer:
Kayla can expect to roll a number 3 approximately 14 times out of 84 rolls of a fair six-sided die, since each roll has a 1 in 6 chance of landing on any given number.
Explanation:
When Kayla rolls a die 84 times, she can expect to roll a 3 in a proportion equal to the probability of rolling a 3 on a single die. A fair six-sided die has a 1 in 6 chance of landing on any given number, including the number 3. Since each roll of the die is independent, we can calculate the expected frequency of rolling a 3 by multiplying the total number of rolls by the probability of rolling a 3.
The calculation is straightforward:
Probability of rolling a 3 = 1/6.Expected frequency of rolling a 3 = Total number of rolls × Probability of rolling a 3.Expected frequency of rolling a 3 = 84 × (1/6) = 14.Therefore, Kayla can expect to roll a 3 approximately 14 times in 84 rolls.
What is the least common multiple of 4 and 6?
Answer:
12
Step-by-step explanation:
Consider the list of multiples
multiples of 4 are 4, 8, 12, 16, 20, ....
multiples of 6 are 6, 12, 18, 24, ....
The least common multiple is 12
NEED HELP ASAP PLEASE IM TRYNA PASS
Answer:
segment SV
Step-by-step explanation:
Observing the figure
we know that
The side that is common to triangle SUV and triangle VTS is only the segment SV
There are no common angles to triangle SUV and triangle VTS
therefore
The answer is the segment SV
HELP A FELLA OUT WILL MARK BRAINLIEST
Answer:
y = 4sin [(1/2)t - (4/3)π ] - 2
Step-by-step explanation:
For this question, do not be intimidated by the terminology, just realize the following:
for y = a sin [ (2π/T) t ]
a = amplitude = given as 4
T = period = given as 4π
phase shift is simply horizontal shift, positive values means the graph moves by that amount to left and negative values means the graph moves to the right.
vertical shift ... is well a shift vertically. positive values move the graph up vertically and negative values move the graph down vertically.
so... if we start with the basic formula:
y = a sin [ (2π/T) t ]
given a = 4 and T = 4π (substitute these values into the formula)
y = (4) sin [ (2π/4π) t ] = (4) sin [ (1/2) t ]
y = 4sin [(1/2)t ]
Now for the shifts:
given phase shift, aka horizontal shift is -(4/3)π, equation becomes
y = 4sin [(1/2)t - (4/3)π ]
given vertical shift is -2, the equation simply becomes
y = 4sin [(1/2)t - (4/3)π ] - 2
Consider the vectors u <-4,7> and v= <11,-6>
See picture for more information. Please help
Answer:
u + v = <7 , 1>
║u + v║ ≅ 7
Step-by-step explanation:
* Lets explain how to solve the problem
- We can add two vector by adding their parts
∵ The vector u is <-4 , 7>
∵ The vector v is <11, -6>
∴ The sum of u and v = <-4 , 7> + <11 , -6>
∴ u + v = <-4 + 11 , 7 + -6> = <7 , 1>
∴ The sum u and v is <7 , 1>
* u + v = <7 , 1>
- The magnitude of the resultant vector = √(x² + y²)
∵ x = 7 and y = 1
∵ ║u + v║ means the magnitude of the sum
∴ The magnitude of the resultant vector = √(7² + 1²)
∴ The magnitude of the resultant vector = √(49 + 1) = √50
∴ The magnitude of the resultant vector = √50 = 7.071
* ║u + v║ ≅ 7
5/6 n=10 what is n in this equation
How do u get straight A’s?
YOU
GOTTA
GET
SCHOOLED!
Study hard and don't let any thing distract you from your goal
Rectangle ABCD is shown on the grid.
The area of rectangle ABCD in square units is_____ .
Anyone know how to do this math problem and if so could you please take your time to explain it in the comments below thank you!
Answer:
34 square units
Step-by-step explanation:
Step 1 : Write the formula for area of rectangle
Area of rectangle = length x breadth
From the graph:
AB = DC
AD = BC
Step 2 : Find the distance between AB and AD to find the length and breadth.
Coordinates : A (-1, 4), B (3, 3)
Distance between two points on AB
Formula : √(x2-x1)² + (y2-y1)²
= √(3-(-1))² + (3-4)²
= √17
Distance between two points on AD
Coordinates of A (-1, 4), D = (-3,-4)
Formula : √(x2-x1)² + (y2-y1)²
= √(-3-(-1))² + (-4-4)²
= √68
Area of rectangle = length x breadth
Area of rectangle = √17 x √68
Area of rectangle = 34
Therefore the area of rectangle = 34 square units
!!
Answer:
34
Step-by-step explanation:
What is the equation of the following line written in general form? (1,6) (6,2)
Answer:
4x+5y-34=0
Step-by-step explanation:
The slope-intercept form of a line is y=mx+b where m is the slope and b is the y-intercept.
My goal is to put in in this form first. Then I will aim to put it in general form, ax+by+c=0.
So let's give it a go:
m is the change of y over the change of x.
To compute this I'm going to line my points up and subtract vertically, then put 2nd difference over 1st difference. Like this:
( 1 , 6)
-(6 , 2)
----------
-5 4
So the slope is 4/-5 or -4/5.
So m=-4/5.
Now we are going to find b given y=mx+b and m=-4/5 and we have a point (x,y)=(1,6) [didn't matter what point you chose here].
6=-4/5 (1)+b
6=-4/5 +b
Add 4/5 on both sides:
6+4/5=b
30/5+4/5=b
34/5=b
So the y-intercept is 34/5.
The equation in slope-intercept form is:
y=-4/5 x + 34/5.
In general form, it is sometimes the goal to make all of your coefficients integers so let's do that. To get rid of the fractions, I'm going to multiply both sides by 5. This clears the 5's that were on bottom since 5/5=1.
5y=-4x+34
Now add 4x on both sides:
4x+5y=34 This is standard form.
Subtract 34 on both sides:
4x+5y-34=0
How do you solve this?
Answer:
It's asking for you to calculate the volume of a cylinder and multiply it by 2/3. This is because the question is asking how much water is in a cylindrical vase with the height and radius.
The formula to calculate the volume of a cylinder is : 3.14 (r^2) (h)
R being the radius and H being the height.
Plug in the values then multiply it all by 2/3
Hoped this help you solve your problem.
[tex]\bf \textit{volume of a cylinder}\\\\ V=\pi r^2 h~~ \begin{cases} r=radius\\ h=height\\ \cline{1-1} r=5\\ h=14 \end{cases}\implies V=\pi (5)^2(14)\implies V=350\pi \\\\\\ \stackrel{\pi =3.14}{V=1099}~\hfill \stackrel{\textit{how much is }\frac{2}{3}\textit{ of that?}}{1099\cdot \cfrac{2}{3}\implies \cfrac{2198}{3}}\implies \stackrel{\textit{rounded up}}{732.7}[/tex]
1. Solve the equation m2 + 6m=-4 using the quadratic formula.
A. m = 5+3
O B. m = 3+V 5
c. m =-3+1 5
D.m=-5+13
Answer:
-3± √5
Step-by-step explanation:
It is given that,
m² + 6m = -4
Points to remember
Solution of a quadratic equation ax² + bx + c = 0
x = [-b ± v(b² - 4ac)]/2a
To find the solution of given equation
m² + 6m = -4
⇒ m² + 6m + 4 = 0
Here a = 1, b = 6 and c = 4
m = [-b ± v(b² - 4ac)]/2a
= [-6 ± √(6² - 4*1*4)]/2*1
= [-6 ± √(36 - 16)]/2
= [-6 ± √20]/2
= [-6 ± 2√5]/2
= -3± √5
Which of the following expressions is equal to
- x^2-36 ?
Answer:
The correct answer is the option "B":
B.(-x-6i)(x-6i)
The expression -x^2-36 can be factored as a difference of squares and is equivalent to -(x+6)(x-6).
Explanation:The expression -x^2-36 can be equivalent to other algebraic forms depending on the manipulation or factoring techniques applied. To simplify or manipulate this expression, one can factor it as the difference of squares. The difference of squares is a pattern where you have an expression in the form of a^2 - b^2, which can be factored into (a+b)(a-b). In the case of -x^2-36, it can be written as -(x^2 - 36), which then can be factored as -(x+6)(x-6). This follows the pattern of a difference of squares since x^2 is the square of x, and 36 is the square of 6.
Learn more about Factoring Algebraic Expressions here:https://brainly.com/question/15066474
#SPJ2
Need to find A, B, and C!
Answer:
Mean: 4.44 add up every number and divide it by how many there is.
Median: 3 put from least to greatest and count till the middle.
Mode: 3 because it appears the most
Answer:
A. Mean = $41900
B. Median = $37000
C. Mode = $37000
Step-by-step explanation:
A. Mean
Here
n=40
Mean = Sum of values/n
[tex]Mean = \frac{(3)(18000)+(3)(22000)+(3)(25000)+(5)(34000)+(17)(37000)+(2)(45000)+52000+(5)(80000)+140000}{40}\\=\frac{54000+66000+75000+170000+629000+90000+52000+400000+140000}{40} \\=\frac{1676000}{40}\\=41900[/tex]
Mean = $41900
B. Median:
As the number of salaries is even,
the median will be mean of middle two terms
[tex]Median= \frac{1}{2}(\frac{n}{2}th\ term+ \frac{n+2}{2}th\ term)\\= \frac{1}{2}(\frac{40}{2}th\ term+ \frac{40+2}{2}th\ term)\\=\frac{1}{2} (20th + 21st)}\\[/tex]
The 20th and 21st term will be 37000
So their mean will be same
So,
Median = $37000
C. Mode
Mode is the value which occurs most of the time in data.
the occurrence of 37000 is highest in the given data.
So,
Mode = $37000 ..
Which set of ratios could be used to determine if one triangle is a dilation of the other
Final answer:
To determine if one triangle is a dilation of another, ratios of corresponding sides must be compared and set up as proportions to see if they are equivalent. When the proportions are equivalent, it indicates a consistent scale factor, confirming a dilation.
Explanation:
To determine if one triangle is a dilation of the other, we compare the ratios of corresponding sides from each triangle. A dilation occurs when all sides of one triangle are in proportion with the sides of a second triangle by the same scale factor. For example, if one triangle has sides of length 3, 4, and 5, and the second triangle has sides of length 6, 8, and 10, then the ratios of the corresponding sides (3/6, 4/8, 5/10) all simplify to 1/2, indicating that the second triangle is a dilation of the first.
To use ratios to determine if one triangle is a dilation of another, you need to set up proportions. For instance, we can express the ratios of corresponding lengths as fractions, and then set each of these ratios equal to the unit scale to form proportions. If the lengths of the triangles are given as 1 inch to 50 inches and 0.5 inches to 5 inches, we can set up the proportion 1/50 = 0.5/5 to show that they are equivalent.
In problems like this, proper notation and maintaining consistency across corresponding dimensions (e.g., width to width and length to length) is essential for accurate comparison.
Examine the quadratic equation: x^2+2x+1=0
A: What is the discriminant of the quadratic equation?
B: Based on the discriminant, which statement about the roots of the quadratic equation is correct?
Select one answer choice for question A, and select one answer choice for question B.
A: 3
A: 0
A: −3
B: There is one real root with a multiplicity of 2 .
B: There are two real roots.
B: There are two complex roots
Answer:
A: 0
B: There is one real root with a multiplicity of 2.
Step-by-step explanation:
[tex]\bf{x^2+2x+1=0}[/tex]
A:The discriminant of the quadratic equation can be found by using the formula: [tex]b^2-4ac[/tex].
In this quadratic equation,
a = 1b = 2c = 1I found these values by looking at the coefficient of [tex]x^2[/tex] and [tex]x[/tex]. Then I took the constant for the value of c.
Substitute the corresponding values into the formula for finding the discriminant.
[tex]b^2-4ac[/tex][tex](2)^2-4(1)(1)[/tex]Simplify this expression.
[tex](2)^2-4(1)(1)= \bf{0}[/tex]The answer for part A is [tex]\boxed{0}[/tex]
B:The discriminant tells us how many real solutions a quadratic equation has. If the discriminant is
Negative, there are no real solutions (two complex roots).Zero, there is one real solution.Positive, there are two real solutions.Since the discriminant is 0, there is one real root so that means that the first option is correct.
The answer for part B is [tex]\boxed {\text{There is one real root with a multiplicity of 2.}}[/tex]
Answer:
A: 0
B: There is one real root with a multiplicity of 2 .
Step-by-step explanation:
Given a quadratic equation:
[tex]ax^2+bx+c=0[/tex]
You can find the Discriminant with this formula:
[tex]D=b^2-4ac[/tex]
In this case you have the following quadratic equation:
[tex]x^2+2x+1=0 [/tex]
Where:
[tex]a=1\\b=2\\c=1[/tex]
Therefore, when you substitute these values into the formula, you get that the discriminant is this:
[tex]D=(2)^2-4(1)(1)\\\\D=0[/tex]
Since [tex]D=0[/tex], the quadratic equation has one real root with a multiplicity of 2 .